2020
DOI: 10.1371/journal.pone.0235815
|View full text |Cite
|
Sign up to set email alerts
|

Complementary epitopes and favorable developability of monoclonal anti-LAMP1 antibodies generated using two transgenic animal platforms

Abstract: Monoclonal antibodies (mAbs) for therapeutic applications should be as similar to native human antibodies as possible to minimize their immunogenicity in patients. Several transgenic animal platforms are available for the generation of fully human mAbs. Attributes such as specificity, efficacy and Chemistry, Manufacturing and Controls (CMC) developability of antibodies against a specific target are typically established for antibodies obtained from one platform only. In this study, monoclonal antibodies (mAbs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The copyright holder for this this version posted November 22, 2023. ; https://doi.org/10.1101/2023.11.22.568300 doi: bioRxiv preprint comprises 50% of all lysosomal membrane proteins and is widely used as a cell surface marker of lymphocyte activation and degranulation. Additionally, LAMP-1 is a physiologically essential protein involved in stabilizing lysosomes and regulating autophagy to prevent embryonic lethality [35,36,37]. The expression of CD107 is associated with a decrease in the expression of CD62L.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted November 22, 2023. ; https://doi.org/10.1101/2023.11.22.568300 doi: bioRxiv preprint comprises 50% of all lysosomal membrane proteins and is widely used as a cell surface marker of lymphocyte activation and degranulation. Additionally, LAMP-1 is a physiologically essential protein involved in stabilizing lysosomes and regulating autophagy to prevent embryonic lethality [35,36,37]. The expression of CD107 is associated with a decrease in the expression of CD62L.…”
Section: Discussionmentioning
confidence: 99%
“…Five thousand events were acquired for each experimental condition and the corresponding images were analyzed using the IDEAS 5 image-analysis software. The internalization score (IS) was then computed as previously described [ 41 ] by using the equation below: …”
Section: Methodsmentioning
confidence: 99%
“…Five thousand events were acquired for each experimental condition and the corresponding images were analyzed using the IDEAS 5 image-analysis software. The internalization score (IS) was then computed as previously described [41] by using the equation below: During the early screening, the normalized IS was plotted. It was the calculated ratio of the IS measured at 37˚C divided by the IS at 4˚C.…”
Section: Antibody Characterization By Flow Cytometry and Internalizationmentioning
confidence: 99%
“…While LAMP-1 comprises 50% of all lysosomal membrane proteins and is widely used as a cell surface marker of lymphocyte activation and degranulation, its exact role remains uncertain. 23 , 24 LAMP-1 is a physiologically essential protein involved in stabilizing lysosomes and regulating autophagy to prevent embryonic lethality. Previous studies have demonstrated limited cell surface expression of LAMP-1 in normal tissues and moderate-to-high membrane expression in a number of breast, colorectal, gastric, prostate, lung, and ovarian tumors, 24 making it a target of interest for oncology applications.…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 24 LAMP-1 is a physiologically essential protein involved in stabilizing lysosomes and regulating autophagy to prevent embryonic lethality. Previous studies have demonstrated limited cell surface expression of LAMP-1 in normal tissues and moderate-to-high membrane expression in a number of breast, colorectal, gastric, prostate, lung, and ovarian tumors, 24 making it a target of interest for oncology applications. Some evidence point to a role for LAMP-1 in tumor progression.…”
Section: Introductionmentioning
confidence: 99%